Making sense of the TTO production function: University technology transfer offices as process catalysts, knowledge converters and impact amplifiers - Antti-Jussi Tahvanainen; Raine Hermans (The Research Institute of the Finnish Economy (ETLA), 2011)
This inductive case study of 7 US university technology transfer offices (TTOs) examines the value added that TTOs contribute to university-industry technology transfer (UITT ). We therefore (i) characterize a set of central organizational TTO practices, (ii) describe how TTOs systemically manage intangible resources to generate these practices, and (iii) describe the conceptual mechanisms through which the practices add value to UITT. The results form an inductive framework that establishes the TTO as (i) a process catalyst that lowers the threshold of UITT stakeholders to engage in technology transfer and to maintain its sustainability, (ii) a knowledge converter that enables congruence between university technology and market needs, and (iii) an impact amplifier that alleviates problems related to the opportunistic incentive structures of UITT stakeholders and maximizes societal impact. The study thus provides new insights into the internal logic of the TTO production function by qualitatively expanding and refining our understanding of the value added generated by TTOs and by helping to comprehend the relationship between inputs and outputs that underlie it.
Keywords: O31; O32; O33; 330; university-industry technology transfer; technology transfer office; organizational practices; intellectual capital; knowledge management